Interleukin-1β in circulating mononuclear cells predicts steatotic liver disease improvement after weight loss in subjects with obesity and prediabetes or type 2 diabetes - Paola Giustina Simeone; Sarah Costantino; Rossella Liani; Romina Tripaldi; Augusto Di Castelnuovo; Armando Tartaro; Alessandro Mengozzi; Francesco Cosentino; Francesco Cipollone; Agostino Consoli; Francesco Paneni; Francesca Santilli (Cardiovascular Diabetology)
Abstract Background Metabolic dysfunction-associated steatotic liver disease (MASLD) is a major cardiovascular risk (CV) factor. Interleukin-1β (IL-1β), a cytokine involved in the pathogenesis of obesity-associated inflammation and type 2 diabetes (T2D), promotes hepatic steatosis. The Canakinumab Anti-inflammatory Thrombosis Outcome (CANTOS) trial showed that the inhibition of the IL-1β pathway was associated with a reduction of CV events in high-risk patients. The present study was designed to determine: (i) whether an equal degree of weight loss by liraglutide or lifestyle changes has a different impact on MASLD extent and IL-1β expression in peripheral blood mononuclear cells from obese subjects with prediabetes or early T2D; (ii) whether baseline IL-1β levels may predict the extent of weight loss and related metabolic changes. Methods Thirty-two obese subjects with prediabetes (n = 16) or newly diagnosed T2D (n = 16), were randomized to the glucagon-like peptide receptor agonist (GLP1-RA) liraglutide or lifestyle counselling until achieving a comparable weight loss. Visceral adipose tissue (VAT) and gene expression of IL-1β in peripheral blood mononuclear cells were assessed by magnetic resonance and real time PCR, respectively. Results At baseline, IL-1β was positively correlated to body mass index (BMI), fasting plasma glucose, HbA1c, VAT, MASLD extent, platelet count, chemerin and interleukin-1 receptor antagonist (IL1-RA). After achievement of the weight loss target in the two groups, a significant but comparable reduction of IL-1β (p for difference = 0.56) was observed in both arms, in parallel with a comparable improvement in glycaemic control, C reactive protein (CRP), BMI and MASLD. Furthermore, basal IL-1β levels independently predicted the extent of MASLD decrease (p = 0.030); subjects in the highest tertile showed a median decrease of − 8.0 (95% CI − 12.3 to − 4.8) compared with − 23.0 (95% CI − 39.5 to − 16.3) in the lowest tertile. Conclusion In patients with obesity with initial impairment of glucose metabolism successful weight loss is associated with a reduction of both IL-1β levels and MASLD degree. Of interest, basal levels of IL-1β predict the extent of MASLD improvement, regardless of the intervention. Our results may set the stage for ad-hoc studies investigating the usefulness of baseline IL-1β a level as a drug-response biomarker. Graphical abstract